Implementing Differentiated Learning to Achieve Deep Learning Within the Context of the Merdeka Curriculum - Dwi Utami; Firmansyah Firmansyah (Green Publisher Indonesia, 2026)
In the era of 21st-century education, the global challenge of achieving deep learning has become increasingly critical, as many education systems continue to struggle with surface-level learning approaches that prioritize memorization over conceptual understanding and critical thinking. This study aims to describe the implementation of differentiated learning as an effort to achieve deep learning within the context of the Merdeka Curriculum in elementary schools. The research was grounded on the premise that each student possesses distinct characteristics, interests, and learning styles, requiring adaptive teaching approaches to optimize their potential. Differentiated learning aligns with the principles of the Merdeka Curriculum, which emphasizes flexibility, meaningful learning, and learner autonomy. This research employed a qualitative method with a case study design conducted in a fifth-grade elementary classroom. Data were collected through observation, interviews, and documentation, and were analyzed descriptively to obtain a comprehensive picture of differentiated learning practices. The findings reveal that instructional differentiation accommodating visual, auditory, and kinesthetic learning styles enhances students’ active engagement, motivation, and conceptual understanding. Moreover, teachers are better supported in managing inclusive classrooms through varied and meaningful learning strategies. The study concludes that differentiated learning plays a vital role in realizing deep learning, in line with the educational transformation agenda of the Merdeka Curriculum.